-36=-72+n

Simple and best practice solution for -36=-72+n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36=-72+n equation:



-36=-72+n
We move all terms to the left:
-36-(-72+n)=0
We add all the numbers together, and all the variables
-(n-72)-36=0
We get rid of parentheses
-n+72-36=0
We add all the numbers together, and all the variables
-1n+36=0
We move all terms containing n to the left, all other terms to the right
-n=-36
n=-36/-1
n=+36

See similar equations:

| n(4n+n)=39 | | 10x-158=3x-18 | | 1/3(6t-5)=t+5/6 | | 6x+29=6(3)+29 | | 9x-1+4x=14x-20 | | 4(1/3)x=260 | | 10+16x=7x+19 | | -2(m-7)=-22 | | 8x+x+7=16 | | 8x+24-2x=54 | | 4*1/3x=260 | | 3n^2-25n+48=0 | | 9x+4=5x+6 | | 41/3x=260 | | 39=x/5+11 | | 1/2n+1/2n+90=180 | | 2u-15=17 | | 5x+3-7(x+1)=7x+3 | | 36=-3(22-y)+(y-4) | | Y+x-22=180 | | 3(2x+50=8x+29 | | 40-b=24 | | 6x+6x-4=3(4x+7) | | 5x-(2x+17)=1 | | 6x^2=810 | | 2c^2-6c-80=0 | | 3/7=5/3y-1/3y | | (f-4)(f-3)=0 | | 9(x=2)+2=9x+2 | | -2/3=4/7b | | X(x+1)=0.24 | | f(9=8)-6+ |

Equations solver categories